Mācību tēmas "Rīgas dārzu un parku arhitektūra" apguve kultūras vēsturē 12. klasē - Mīlgrāve, Ieva (Latvijas Universitāte, 2008)
Diplomdarbs: „Mācību tēmas Rīgas dārzu un parku arhitektūra apguve kultūras vēsturē 12. klasē” sastāv no ievada, četrām nodaļām, nobeiguma, avotu saraksta, pielikumiem. Diplomdarba mērķis – izpētīt, kāda nozīme kultūras vēstures tēmas „Rīgas dārzu un parku arhitektūra” apguvē ir veiksmīgi izvēlētām mācību metodēm un mācību darba organizācijas formām. Pirmajā diplomdarba nodaļā atlasīta literatūra un avoti par Rīgas dārziem un parkiem, veikta tās analīze. Otrajā nodaļā izpētīta, analizēta pedagoģiski psiholoģiskā literatūra, avoti par mācību metodēm un mācību darba organizācijas formām. Trešajā nodaļā izveidots mācību saturs tēmai „Rīgas dārzu un parku arhitektūra”. Ceturtajā nodaļā analizēts izstrādātais mācību plāns un izvērtēti rezultāti. Atslēgvārdi: kultūras vēsture, kultūrvēsturiskais mantojums, dārzi, parki, mācību metodes.

Diploma paper: “Acquisition of a subject Architecture of Riga’s gardens and parks in classes of Cultural history in form 12” consists of introduction, four chapters, conclusion, bibliography and appendices. Purpose of the diploma paper – to investigate the importance of successfully selected teaching methods and organizational forms of the study work in acquiring the subject „Architecture of Riga’s gardens and parks” in classes of Cultural history. Within the framework of the first part of the diploma paper literature and information on gardens and parks of Riga has been selected and analysed. In the second part pedagogical and psychological literature, as well as literature sources on teaching methods and organizational forms of study work have been studied and looked at in depth. The third part includes developed study content for the subject „Architecture of Riga’s gardens and parks”. The fourth part, in its turn, consists of approbation of the developed study plan and evaluation of results. Keywords: cultural history, cultural and historical heritage, parks, gardens, learning method. 3
Acquisition of the theme "The architecture of Riga gardens and parks" in Grade 12 at history of culture lessons
Keywords: Pedagoģija